POLA PENGELUARAN MAHASISWA PENDIDIKAN EKONOMI DI MASA PANDEMI COVID-19 - Andrew Christian Aseng; Lanny Cantika Stevanie Pongoh (Nusantara Hasana Journal, 2022)
This research was conducted to find out spending pattern of the Economic Education students at Universitas Klabat were like during the COVID-19 pandemic. This study uses a quantitative and qualitative method with a questionnaire adapted from several previous studies. A total of 35 students from the study program participated in this research. The data obtained were processed using descriptive statistical technique of percentage. The results of the study found that there has been an increase in spending since the pandemic occurred with expenditures for the categories of food, telephone and internet packages, college needs, and personal needs that rose significantly. Furthermore, while the average monthly expenditure of students on food is almost evenly distributed in each nominal, the average monthly expenditure for other categories is mostly below Rp. 200,000.